Resultantes geo-hidroecológicas do ciclo cafeeiro (1780-1880) no médio vale do rio Paraíba do Sul: uma análise quali-quantitativa - Dantas, Marcelo Eduardo; Coelho Netto, Ana Luiza (Anuário do Instituto de Geociências, 1996)
The coffee cycle represented a period of intense morphodynamic activity, proceeding by a general deforestation. On the Paraíba do Sul Middle Valley, this economic cycle lasted 100 years aproximately (1780-1880). Historical documents, radiocarbon dates and volumetric measurements of the valley fills correlated from the coffee time, have provided informations on the environmental impact, particularly associated with climatic and hidro-erosive processes both on the hillslopes and fluvial domains. Deforestation introduced a drought period up to 6 months and also to an increasing frequency of intense rainstorms, particularly in the summer. Along the Piracema river valley, sedimentation rates attained about 70.000mÂ³km/year. Transfering this volume to the source-area on the hillslopes, it gives an estimate relief downwearing around 7,5 cm depth, resulting on the removal of the organic rich A horizon and showing so, the catastrophic effect of this economic activity, resulting in an extremely wasted degraded landscape.